2010
DOI: 10.1111/j.1751-7133.2010.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Pulmonary Arterial and Pulmonary Venous Hypertension and the Implications for Therapy

Abstract: Pulmonary arterial and pulmonary venous hypertension develop from distinctly different etiologies. Pulmonary arterial hypertension (PAH), or Group 1 pulmonary hypertension (PH), is a precapillary PH that arises idiopathically or as the result of a divergent array of causes, including connective tissue disease. Pulmonary venous hypertension (PVH), or Group 2 PH, primarily manifests as a postcapillary PH in the setting of left heart failure or valvular disease. A subset of PVH patients, however, develop a reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…PH due to left heart disease is the most common cause of PH [1]. It affects primarily the pulmonary venous bed [2] and is therefore also called pulmonary venous hypertension (PVH) or postcapillary PH [3]. This aspect plays a pivotal role in the therapy of PVH, as vasodilators that act predominantly in the pulmonary arterial bed may increase the pulmonary perfusion and thereby enhance hydrostatic pressure, pulmonary edema and total pulmonary vascular resistance (PVR) [1].…”
Section: Introductionmentioning
confidence: 99%
“…PH due to left heart disease is the most common cause of PH [1]. It affects primarily the pulmonary venous bed [2] and is therefore also called pulmonary venous hypertension (PVH) or postcapillary PH [3]. This aspect plays a pivotal role in the therapy of PVH, as vasodilators that act predominantly in the pulmonary arterial bed may increase the pulmonary perfusion and thereby enhance hydrostatic pressure, pulmonary edema and total pulmonary vascular resistance (PVR) [1].…”
Section: Introductionmentioning
confidence: 99%
“…4 Shortness of breath is the most frequently symptoms of pulmonary hypertension. 5 In the present study, the authors indicated the recovery in pulmonary function tests by bronchodilator therapy but it was not correlated with the improvement in Borg dyspnea measurements. Undiagnosed or untreated pulmonary hypertension may cause the reason of this result.…”
mentioning
confidence: 56%
“…Patients with diastolic HF are at an increased risk of developing irreversible PH (precapillary PH) [ 46 ]. Whereas passive postcapillary PH frequently is reversible and likely to improve, the vascular remodeling of precapillary PH may not regress after surgical and medical treatment of the underlying cardiac disease [ 46 ]. PH commonly is diagnosed by TTE or by invasive rightheart catheterization, and is a marker of poor prognosis in patients with HF [ 47 ].…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…Therefore some patients develop elevated TPG (>10 mmHg) and pulmonary vascular resistance (PVR >2.5-3 Wood units), and these changes in TPG and PVR indicate the development of irreversible precapillary PH [ 44 , 46 ]. Patients with diastolic HF are at an increased risk of developing irreversible PH (precapillary PH) [ 46 ]. Whereas passive postcapillary PH frequently is reversible and likely to improve, the vascular remodeling of precapillary PH may not regress after surgical and medical treatment of the underlying cardiac disease [ 46 ].…”
Section: Preoperative Assessmentmentioning
confidence: 99%